The extent of Algeria's commitment to preventing money laundering in financial institutions - sahnoune, nassim (Journal of Research in Finance and Accounting, 2021)
This study aims to emphasize the importance of money laundering prevention controls in protecting and sustaining Algerian financial institutions in light of relying on the recommendations of the International Financial Action Group, which is one of the international standards in combating money laundering and terrorist financing. Two MENAFATF reports were adopted: Mutual Evaluation Report 2010 and Follow-up Report 2016. The study concluded that Algeria contributes to the commitment to implement controls to prevent money laundering in financial institutions to a large extent.